MEMBANGUN JIWA KEWIRAUSAHAAN BAGI GENERASI MUDA (GEN Z) DENGAN PEMANFAATAN SOSIAL MEDIA PADA ERA DIGITALISASI - Amelia Josefien Viotty Radianto; M. Rifkhi Fauzan S; Trisye Natalia Kilay; Chrisye Saija; Maria D. I. Renleeuw; Thalya N. Christine (LPPM Universitas Bina Bangsa, 2023)
The purpose of this community service activity is to provide training to foster entrepreneurial spirit to gen Z by utilizing social media. The method used to carry out this community service activity is in the form of training to 50 gen Z people in Ambon City. To evaluate service activities, the service activity team distributed questionnaires related to entrepreneurship to the participants. The result of the service activities was that the entrepreneurial spirit of the participants grew significantly in all aspects such as the aspect of feeling of interest increased by 20%, the aspect of feeling happy increased by 12%, and the aspect of motivation and the aspect of desire / hope which both increased by 19%